2022
DOI: 10.7759/cureus.31626
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glycosylated Haemoglobin (HbA1c) Level With Left Ventricular Diastolic Dysfunction in Patients With Type 2 Diabetes

Abstract: BackgroundSome literature has shown a high prevalence of pre-clinical diastolic dysfunction in subjects with type 2 diabetes mellitus. The current study was carried out to determine the association of glycosylated hemoglobin (HbA1c) levels with left ventricular diastolic dysfunction (LVDD) in patients with type 2 diabetes. MethodsAn observational cross-sectional study was conducted in a tertiary health care center in Jharkhand. A total of 100 subjects diagnosed with type 2 diabetes mellitus who gave informed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Significant associations between long-term glycemic status quantified as HbA 1c and parameters of diastolic and systolic dysfunction were reported in multiple studies, where the cardiac function of T2DM patients was evaluated by means of echocardiography have reported [59]. Based on univariate and multivariable analyses, Guria et al concluded that higher levels of HbA 1c increased the risk of LVDD (OR 1.26) [60]. Other researchers found that HbA 1c was not associated with LVDD in T2DM overweight/obese patients [61].…”
Section: Diastolic (Dys)function and Cardiovascular-related Resultsmentioning
confidence: 99%
“…Significant associations between long-term glycemic status quantified as HbA 1c and parameters of diastolic and systolic dysfunction were reported in multiple studies, where the cardiac function of T2DM patients was evaluated by means of echocardiography have reported [59]. Based on univariate and multivariable analyses, Guria et al concluded that higher levels of HbA 1c increased the risk of LVDD (OR 1.26) [60]. Other researchers found that HbA 1c was not associated with LVDD in T2DM overweight/obese patients [61].…”
Section: Diastolic (Dys)function and Cardiovascular-related Resultsmentioning
confidence: 99%